Sikkim Black goats – characters, management and microsatellite based genetic proile - N K Verma; Pushp Raj Shivahre; RAK Aggarwal; Rekha Sharma; PS Dangi; NT Bhutia (Journal of Livestock Biodiversity, 2025)
Sikkim Black goats are distinct from Singharey goats, the main population of Sikkim state, in respect of coat colour, type of horns and their size. Data on phenotypic and biometric traits was generated on 93 animals belonging to different locks in their native tract. Blood samples were collected from genetically unrelated animals. Sikkim Black goats are of medium body size. Head is proportionate to body. Nose is straight. The horns are strong, broader at base, pointed tip, grey in colour, curving backward. Muzzle is black, hooves are grey. Underbelly is also black. Beard is seen in few animals of both sexes. These goats are slightly shorter than Singharey goats but their face, horn and tail are comparatively longer. The mean estimates for height at withers, body length, Chest/heart girth, paunch girth, face length, horn length, ear length and tail length in adult ( >18 months) female goats were 50.06±0.85, 58.75±0.73, 70.65±0.73, 79.57±1.17, 17.11±0.20, 10.17±0.53, 12.70±0.23, 10.35±0.24 cm, respectively whereas for males the average measurements were 54.70±1.19, 61.80±1.39, 75.97±1.48, 82.30±1.76, 17.90±0.29, 15.070±.77, 13.50±0.36 cm. The average body weight for adult females was 28.48±0.72 kg and males 34.87±1.56 kg. Observed number of alleles varied from 2 to 9 with mean value 5.391±0.411, effective number varied from 1.145 to 6.400 with mean 2.771±0.261. Observed heterozygosity (Ho) was less than the expected (He) at most of the loci leaving ILSTS008, ILSTS005, ILSTS0087, ILSTS0029 and ILSTS034. The values ranged from 0.125 to 0.882 with mean 0.420±0.038for observed and 0.127 to 0.844 with mean 0.575±0.035 for expected heterozygosity. Shannon’s information index value varied from 0.291 (ILSTS029) to 1.950 (ILSTS030) with mean value 1.168±0.085. F estimates varied from -0.175 ( ILSTS087) to 0.835 (ILSTS058) with mean value 0.239±0.058. The population also exhibited HW equilibrium w.r.t. ten loci where chi square values were non-signi icant. A normal ’L’ shaped distribution of mode–shift test, non-signi icant heterozygote excess suggested absence of bottleneck in the existing Sikkim Black goat population. The study concluded that there was a reduction in genetic variability in Sikkim Black goat population. Looking at the distinct phenotype but sharing the breeding tract with Singharey goats, there is a need to conserve and propagate the population through appropriate scienti ic management.